The official history of the Falklands Campaign. - Freedman, Lawrence (Government official history series., 2005)
This official history of the Falklands Campaign covers the origins of the 1982 war, describing the history of the dispute between Argentina and Britain over sovereignty. In 1982 an apparently trivial incident over an illegal landing by scrap-metal merchants turned into a major crisis.